(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Filters are used in electronic circuits to remove the unwanted frequency components from desired signals. A digital filter basically provide high attenuation to the unwanted ones and offer very low or ideally zero attenuation to desired signal components when itâ€™s impulse response is adjusted as per requirement. For ideal filters, the length of such an impulse response is infinite and also the filter will be non-causal and unrealizable. So, we need to truncate this infinite impulse response to make it finite. For this truncation, we use window functions. Using window functions, we obtain a finite impulse response or simply FIR filter. The shape of a window in time domain decides the characteristics of resultant filter in frequency domain. Several window functions are available in literature. For the present work we have choosen the three parameter Cosh window for truncation of infinite impulse response. It is also called as modified Cosh window because it has been obtained byÂ inserting a third parameter in the basic 2-parameter Cosh window function. The main goal of this work is to study this modified Cosh window and design a digital low pass FIR filter using the same in MATLAB. First of all the properties of window function are described and frequeny domain responses ofÂ window function is obtained. Then FIR filter is analyzed using window design method and itâ€™s characteristics have also been studied in frequency domain.